Feasibility Analysis of Corn Farming with a Partnership Pattern in Pringgabaya District, East Lowbok District - Ridwan Ridwan; Muhsin Muhsin; Zuhriatun Solihah (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2023)
This research was carried out in Pringgabaya District, East Lombok Regency. This research aims to find out: (1). Model of partnership pattern between corn farmers and PT. DNYA Perbawa Pradhikasa, (2). Feasibility of corn farming with a partnership pattern with PT. DNYA Perbawa Pradhikasa, (3). The obstacles faced by corn farmers in Pringgabaya District, East Lombok Regency in partnering with PT. Donly Perbawa Pradhikasa. ). Labuhan Lombok Village and North Pringgabaya Village were selected as research locations and this location was determined using a purposive sampling technique, using 30 respondents determined proportionally. Random sampling and data collection was carried out using direct interview techniques with respondents, using questionnaires that had been prepared and carried out in the month July 2023To find out Total Production Costs (Total Cost) can be calculated using the formula TC = FC+VC, Total Revenue: (Total Revenue) with the formula TR = P x Q, Income: π = TR-TC, meanwhile to find out the feasibility of corn farming you can calculated using Revenue Cost Ratio (RCR) analysis. The results of the research show that the average income from corn farming in Pringgabaya District, East Lombok Regency is IDR 10.894,928., per ha (MH 2021/2022), with an R/C Ratio value of 1.650. This means that corn farming in Pringgabaya District, East Lombok Regency using a Partnership Pattern is feasible to develop. Meanwhile, the problems faced in corn farming with a partnership pattern are: high fertilizer prices, pest and disease attacks, water content agreements, price suitability and capital adequacy.